Facile synthesis of ZrO2 coated BiOCl0.5I0.5 for photocatalytic oxidation-adsorption of As(III) under visible light irradiation - Zhiyao Ma; Mengya Zhang; Jingyuan Guo; Liu, Wen; Meiping Tong (Chemosphere, 2018)
ZrO2 modified BiOCl0.5I0.5 composites (ZBCI), synthesized via a facile precipitation method at room temperature, were utilized to photocatalytically oxidize and adsorb arsenite from water under visible light irradiation. The composites were well characterized by using various techniques. With visible light irradiation, 5 mg L−1 of As(III) could be completely removed by ZBCI (0.25 g L−1) in 90 min. Particularly, we found that ZBCI composites not only could oxidize As(III) into As(V) with visible light irradiation, but also could effectively capture the generated As(V), leading to the negligible residual As(III) or As(V) in aqueous solutions after 90 min treatment. In the fabricated composites, ZrO2 acted as the main adsorption sites while BiOCl0.5I0.5 served as the primary photocatalysis center. Because of the heterostructure of ZBCI, e- generated by BiOCl0.5I0.5 would be transferred to ZrO2 and inhibited e–h+ recombination rate, contributing to the improved photocatalytic efficiency. ZBCI could effectively remove As(III) over a broad range of pH from 3 to 11. Chloride and nitrate did not obviously affect the photocatalytic As(III) removal, while sulfate and phosphate yet reduced the capture of As(III). Moreover, ZBCI composites exhibited high photocatalytic As(III) removal efficiency during the fourth reused cycles. The facile synthesized ZBCI could be employed to capture and oxidize As(III) from water.
Keywords: Adsorption; Arsenic; Photocatalytic oxidation; Visible light irradiation; ZrO-BiOClI